2013
DOI: 10.1038/ni.2556
|View full text |Cite|
|
Sign up to set email alerts
|

Control of amino-acid transport by antigen receptors coordinates the metabolic reprogramming essential for T cell differentiation

Abstract: Summary T lymphocytes regulate nutrient uptake to meet the metabolic demands of immune activation. The present study shows that the intracellular supply of large neutral amino acids (LNAAs) in T cells is regulated by pathogen and the T cell antigen receptor (TCR). A single System L transporter, Slc7a5, mediated LNAA uptake in activated T cells. Slc7a5-null T cells could not metabolically reprogram in response to antigen and failed clonal expansion and effector differentiation. The metabolic catastrophe caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
909
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 769 publications
(950 citation statements)
references
References 41 publications
33
909
0
8
Order By: Relevance
“…Availability of nutrients is another critical requirement for mTORC1 activation in T cells. TCR signaling increases amino acid uptake, which is essential for mTORC1 activation (18). We therefore determined surface expression of the amino acid transporter CD98.…”
Section: Resultsmentioning
confidence: 99%
“…Availability of nutrients is another critical requirement for mTORC1 activation in T cells. TCR signaling increases amino acid uptake, which is essential for mTORC1 activation (18). We therefore determined surface expression of the amino acid transporter CD98.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the BCAT1 gene has been shown to be a direct target for c-myc activation (55). Recently, c-myc has been shown to play a vital role in CD8 ϩ T cell effector function (22). In these studies, c-myc was shown to up-regulate the glycolytic machinery necessary for T cell activation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, c-myc has been shown to play a vital role in CD8 ϩ T cell effector function (22). In these studies, c-myc was shown to up-regulate the glycolytic machinery necessary for T cell activation (22). The fact that BCATc Ϫ/Ϫ T cells demonstrate enhanced glycolysis suggests that up-regulation of BCATc represents a negative feedback loop in this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naïve and memory T cells use catabolic metabolism via oxidative phosphorylation, especially fatty acid oxidation, to produce ATP for their survival. In contrast, antigen-stimulated T cells switch to anabolism to support their rapid proliferation through up-regulating expression of genes involved in multiple metabolic pathways, including glycolysis, fatty acid and cholesterol biosynthesis, and amino acid transport (7)(8)(9)(10). Emerging studies indicate that distinct metabolic pathways contribute to the fate decisions of effector and memory T cells.…”
mentioning
confidence: 99%